Epidemiology of Traumatic Tusk Fractures of Managed Elephants in North America, South America, Europe, Asia and Australia - Josephine B. Rose; Austin Leeds; Rachel LeMont; Linda M. Yang; Melissa A. Fayette; Jeffry S. Proudfoot; Michelle R. Bowman; Allison Woody; James Oosterhuis; David A. Fagan (Journal of Zoological and Botanical Gardens, 2022)
Elephant tusk fractures are a management and medical challenge that can escalate into life-threatening complications. Here, an international survey was sent to elephant managers to understand the risk factors associated with tusk fractures since 2009, identifying best practices for reducing the incidence. Out of 459 elephants included in the survey, 85 elephants incurred at least one fracture. Though not statistically significant, descriptive statistics identified a trend for both Asian and African elephant males to be more likely to incur a fracture than females. Additionally, the first reported fracture occurred in males of both species approximately ten years earlier in age than females. The most common causes of fractures were conspecific interactions (44.6%), caught tusk in an enclosure or enrichment item (28.4%), and a strike by the elephant of a tusk with an object (12.2%). For social causes, unstable hierarchy (45.5%) and specific agonistic interactions (36.4%) were the most frequently cited fracture causes. Steel gates were associated with 23.8% of fractures caused by enclosure elements. Management changes including tusk trimming, enrichment, training, and re-arranging social groups were found to be important in reducing subsequent fractures, with odds ratios showing that a second tusk fracture was 6.37 times more likely to occur if no management changes occurred after the first fracture. Our data suggests that targeted management strategies in herds with maturing males, unstable social dynamics, and/or high-risk enclosure elements could reduce the frequency of tusk fractures.